Factors influencing waist circumference among urban bank employees in Northeast Ethiopia: a cross-sectional study - Yimer, Woynshet; Asmare, Lakew; Gebeyehu, Fikre Bayu; Alemu, Tihtna; Mehamed, Anisa; Yeshanew Ayele, Fanos (Frontiers in Nutrition, 2025)
IntroductionA widely recognized public health issue affecting people worldwide is central obesity. Numerous chronic conditions, such as type 2 diabetes mellitus, cardiovascular disease, and malignancies are linked to this syndrome. There is limited information about waist circumference (WC) and its related variables among urban bank workers in Ethiopia. Therefore, the purpose of this study was to evaluate waist circumference and the factors associated with it among bank workers in Northeast Ethiopia.MethodsAn institution-based cross-sectional study was carried out in Dessie, Northeast Ethiopia, between 2 October 2023 and 24 October 2023. A random selection method was employed to select 363 bank workers. STATA version 17 was used for analysis after the data were imported into EpiData version 4.4.2.0. Univariate and multivariate linear regression analyzes were performed to identify factors related to waist circumference. Normality, homoscedasticity, significant outliers, and multicollinearity were assessed, and a p-value of less than 0.05, along with a 95% confidence interval, was considered statistically significant.ResultsA total of 345 participants were included in the final analysis, with a 95% response rate. The overall mean ± standard deviation (SD) of the waist circumference of the employees was 81.7 ± 6.8 cm, with 82.4 ± 6.5 cm for men and 80.7 ± 7.2 cm for women. The overall prevalence of central obesity was 57.7%, with 48.2% for the men and 70.3% for the women. The overall mean ± SD of the waist-to-hip ratio (WHR) was 0.90 ± 0.05, with 0.91 ± 0.04 for men and 0.89 ± 0.05 for women. The average waist circumference was significantly associated with the participants’ age (0.2 cm per year (SE: 0.1)) and MET hours (0.2 cm (SE: 0.1)). The mean waist circumference was 2.7 cm (SE:0.8) higher in the married women, 4.6 cm (SE:1.9) higher in the participants with non-communicable diseases (NCDs), and 1.7 cm (SE:0.8) higher in the participants who consumed discretionary calories for 4 days/week.ConclusionThe mean waist circumference among bank employees was higher, with more than half of the participants having central obesity. Age, marital status, discretionary calorie intake, non-communicable diseases, and metabolic equivalence task hours were the significant factors of waist circumference. Therefore, promoting activities aimed at preventing non-communicable diseases, such as leisure-time physical activity, and reducing discretionary calorie intake are essential for reducing high waist circumference measurements.